2021
DOI: 10.1039/d1ra01906f
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of boron from brines with high magnesium content by solvent extraction using aliphatic alcohol

Abstract: The multi-stage counter-current simulation process showed an extraction system with great potential for commercial application in boron recovery from salt lake brines with high magnesium content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
6
0
11
Order By: Relevance
“…Several authors (Ayers et al, 1981;Bachelier and Verchere, 1995;Grinstead, 1972;Peng et al, 2018;Xu et al, 2021) reported that boric acid is extracted by mono-alcohols or di-hydroxy alcohols from low to high ionic strength aqueous solutions by an esterification reaction. For instance, Fan et al (2018) mentioned that the extraction of boric acid with 2-ethyl-1,3-hexanediol occurs according to the following esterification reaction:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors (Ayers et al, 1981;Bachelier and Verchere, 1995;Grinstead, 1972;Peng et al, 2018;Xu et al, 2021) reported that boric acid is extracted by mono-alcohols or di-hydroxy alcohols from low to high ionic strength aqueous solutions by an esterification reaction. For instance, Fan et al (2018) mentioned that the extraction of boric acid with 2-ethyl-1,3-hexanediol occurs according to the following esterification reaction:…”
Section: Resultsmentioning
confidence: 99%
“…Many papers investigated solid/liquid extraction (adsorption, ion exchange resin (Guan et al, 2016;Gazi and Bicak, 2007)), (electro)membrane operation (electrodialysis, reverse osmosis (Melnik et al, 1999;Farhat et al, 2013)), chemical precipitation (Shih et al, 2014) and liquid-liquid extraction (Bicak et al, 2005;Joshi et al, 2012;Karakaplan et al, 2004;Brooks et al, 2018) to recover boron from various aqueous solutions including wastewater and brines (Kim et al, 2023). Electrodialysis, ion exchange resins and chemical precipitation are not highly selective towards boron (Xu et al, 2021;Peng et al, 2021). Adsorption requires many stages and consumes an important amount of fresh water (Bonin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Among them, liquid-liquid extraction is the most used technology in hydrometallurgy for the recovery of many metals including boron. 21,22 Alcohols [23][24][25] diluted in kerosene, 12 toluene, 26 chloroform, 19,25 benzene 27 or sulfonated kerosene 23,24,28,29 were extensively reported in the literature as extractants to recover boron from brines.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a pH buffer is required to prevent ester hydrolysis in an acidic environment. It is common practice to classify boron extraction agents as either mono‐hydroxy alcohols (2‐butyl‐1‐n‐octanol), 22–24 di‐hydroxy alcohols (diols), 25,26 or phenols 27 . Alcohols with 8–12 carbon atoms, such as 2‐ethyl‐1,3‐hexanediol (EHD), 28 2‐butyl‐2‐ethyl‐1,3‐propanediol (BEPD), 29,30 and 2,2,4‐trimethyl‐1,3‐pentanediol, 31 have been shown to have excellent boron extraction efficiencies. normalBnormalOH3goodbreak+2normalRnormalOH2B()normalRO22goodbreak+3H2normalOgoodbreak+H+0.12emwith0.24emnormalRnormalOH2goodbreak=generic0.12emnormaldialcohol …”
Section: Introductionmentioning
confidence: 99%